2020
DOI: 10.1007/s12291-020-00901-w
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Intrinsic and Extrinsic Coagulation Pathway Factors in OCP Treated PCOS Women

Abstract: Human polycystic ovary syndrome (PCOS)-a cluster of diseases displays various symptoms associated with endocrine and gynecological disorders in childbearing women. Oral contraceptive pills (OCP) being a drug of choice minimizes symptoms and complications associated with the disorder. But, the controversial data available in literature regarding use of OCPs compels us to setup a study design regarding effect of OCP treatment in PCOS subjects and the possible outcomes specifically regarding coagulation pathways.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Since the pathophysiology of PCOS is multifactorial, the possibility of genetic variants influencing the clinical outcomes should be duly considered, especially while choosing the right treatment regimen. In our earlier publications also, we have observed that inflammation and coagulation markers are deranged in PCOS women, especially those taking OCP as treatment,[ 50 51 52 53 ] thus, anti-inflammatory and insulin-sensitizing therapeutics are recommended in addition to lifestyle interventions. Our study’s limitation is that we were unable to conduct expression studies at the mRNA level that would have assisted in identifying the molecular processes by which these SNPs exert their effect.…”
Section: Discussionmentioning
confidence: 99%
“…Since the pathophysiology of PCOS is multifactorial, the possibility of genetic variants influencing the clinical outcomes should be duly considered, especially while choosing the right treatment regimen. In our earlier publications also, we have observed that inflammation and coagulation markers are deranged in PCOS women, especially those taking OCP as treatment,[ 50 51 52 53 ] thus, anti-inflammatory and insulin-sensitizing therapeutics are recommended in addition to lifestyle interventions. Our study’s limitation is that we were unable to conduct expression studies at the mRNA level that would have assisted in identifying the molecular processes by which these SNPs exert their effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, OCPs are associated with venous thrombosis, stroke and derangement of several metabolic parameters in the general population [ 20 , 21 ]. Earlier, we reported on the repercussions of OCPs on the concentration of metabolic, coagulation and inflammatory markers in serum among women with PCOS [ 22 25 ]. However, there is a lack of literature at the molecular level on the various effects of OCPs on women with PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in cases of gynecological problems, failure to continue OCP could lead to difficulties in controlling symptoms, exacerbation of disease, and greater distress. Thus, the prevalence of dysmenorrhea is more likely in women not using OCP [ 13 ], though in polycystic ovary syndrome, the use of OCP can have adverse consequences [ 14 ]. In fact, the main reason for non-adherence is the fear of becoming seriously ill [ 15 ], while prior use of such treatment and educational talks about the problems of hormone therapy significantly improve the continuation rate, preventing the various problems for which it was prescribed.…”
Section: Introductionmentioning
confidence: 99%